The Role of Authorities at Central and Local Level for Social Policy - Valkov, Vladimir (Research Papers, 2018)
The management and administration of social policy are essential for the quality of service to citizens. At central level, social policy bodies are the Ministry of Labor and Social Policy, the National Social Security Institute and the National Revenue Agency. The local authorities implementing the social policy are the Regional Social Security Administration (ROSO) and the Territorial Units (TA) of the NRA.
Keywords: Social policy and administrative structure; Rousse; NSSI; NRA; TA